Hail Mary! The Religious Devotion Presented in the Movie The Auto of Compadecida (Revista Internacional de Folkcomunicação, 2018)
ABSTRACT This article analyzes the appropriation process of the elements of popular culture by the mass media, having as object of study the representation of the Holly Mary devotion in the cinematographic work “The Auto of Compadecida”. The devotion to Holly Mary consists in a remarkable manifestation of Brazilian popular culture and religiosity, through the analysis of this representation, based on theories of the Discourse Analysis, Folkcommunication and Cultural Studies, is possible to identify the dramaturgical marks inserted in the audiovisual work they represent in the religious devotion. KEY-WORDS Popular Culture; Holly Mary Devition; “O Auto da Compadecida”.